2019
DOI: 10.3389/fimmu.2019.02189
|View full text |Cite
|
Sign up to set email alerts
|

Application of Flow Cytometry in the Diagnostics Pipeline of Primary Immunodeficiencies Underlying Disseminated Talaromyces marneffei Infection in HIV-Negative Children

Abstract: Talaromyces (Penicillium) marneffei is an AIDS-defining infection in Southeast Asia and is associated with high mortality. It is rare in non-immunosuppressed individuals, especially children. Little is known about host immune response and genetic susceptibility to this endemic fungus. Genetic defects in the interferon-gamma (IFN-γ)/STAT1 signaling pathway, CD40/CD40 ligand- and IL12/IL12-receptor-mediated crosstalk between phagocytes and T-cells, and STAT3-mediated Th17 differentiation have been reported in HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 67 publications
0
40
0
Order By: Relevance
“…In highly endemic regions in northern Thailand, Vietnam and southern China (Guangdong, Guangxi and Hong Kong) [2][3][4][5][6], the prevalence of talaromycosis as an HIVassociated opportunistic infection (OI) is only lower than that of tuberculosis and cryptococcosis [2,3]. The incidence of talaromycosis is also increasing in the HIV-negative population due to the expanding use of immunosuppressive drugs and chemotherapy and the rising number of solid and bone marrow transplantations [7][8][9]. Evidence suggests that the endemic areas of talaromycosis are increasing due to improved mass transportation and global warming [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In highly endemic regions in northern Thailand, Vietnam and southern China (Guangdong, Guangxi and Hong Kong) [2][3][4][5][6], the prevalence of talaromycosis as an HIVassociated opportunistic infection (OI) is only lower than that of tuberculosis and cryptococcosis [2,3]. The incidence of talaromycosis is also increasing in the HIV-negative population due to the expanding use of immunosuppressive drugs and chemotherapy and the rising number of solid and bone marrow transplantations [7][8][9]. Evidence suggests that the endemic areas of talaromycosis are increasing due to improved mass transportation and global warming [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Infection has been widely suggested to be an indicator disease for differential diagnosis in HIV-infected patients [ 4 , 5 , 7 ]. In recent years, it has been reported that an increasing number and proportion of cases in non-HIV-infected patients who had some form of immunodeficiency (hypogammaglobulinemia, CD4 lymphopenia) or underlying diseases with immunocompromised condition, including hematologic malignancies or autoimmune diseases, were receiving treatments that could impair their cellular immunity, such as antineoplastic or corticosteroid agents [ 8 , 9 ]. However, some researchers have recommended that T. marneffei infection also occur in persons with normal immunity [ 4 , 8 , 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…T. marneffei can cause a life-threatening systemic infection in immunocompromised individuals, especially HIV-positive patients (Woo et al, 2012). In recent years, T. marneffei has become a leading AIDS-defining diagnosis in Southern Asia, trailing only tuberculosis and cryptococcosis in incidence (Wu et al, 2008;Le et al, 2011;Hien et al, 2016;Lee et al, 2019). Furthermore, T. marneffei infection has recently been increasingly observed in HIV-negative adults with no reported immunosuppressive condition, but immunodeficiency is suspected to be the cause of these infections (Ramos-e-Silva et al, 2012;Kauffman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%